Development of a Typical Hourly Electricity Consumption Profile for Student Residence Halls Based on Central Tendency Method - Amber, K. P.; Aslam, W.; Bashir, M. A. (The Nucleus, 2016)
Actual measured hourly electricity consumption profile (HEP) helps the building engineer in numerous ways, e.g. for the optimum and accurate sizing of a solar PV for their building, for identifying abnormal peaks and drops, for negotiating with utility supplier etc. Conventional electricity meters do not have features to provide hourly consumption; instead these provide daily or monthly consumption. In such situation, it becomes difficult to make a precise estimate of building’s hourly consumption and a reliable and quick method is desired to estimate hourly consumption. Using four years of measured hourly electricity consumption data for three residence halls, this paper aims to use the central tendency method to develop a dimensionless typical HEP for this building category. Based on the skewed nature of hourly data distributions, median was selected as suitable measure of central tendency. Therefore, using the hourly median values, a typical HEP was developed. The proposed HEP was tested and compared with the actual HEPs of three other similar buildings and it was found that the estimated HEPs matched very well with actual HEPs with a maximum hourly RMSE of 0.9%. Finally, limitations of the proposed HEP are discussed and some recommendations are made in this regard.